THE ADMINISTRATION OF COLLEGE COURSES IN ACCOUNTING. - Bennett, George E. (The Accounting Review, 1927)
Abstract The article comments on the article by Professor Chapman in the December, 1926 issue of "The Accounting Review" ominously entitled, "The Administration of College Courses in Accounting." It was indeed with surprise and perturbation that the writer attempted to digest the list of administrative problems; he was surprised at the number presented and perturbed by the fact that in nearly fifteen years of contact with school accounting curricula he had not even imagined that the problems were as difficult and far-reaching in effect as intimated. Basically, the questions raised by Professor Chapman may be answered from the point of view of two considerations: money and results. Money greases the wheels of accounting departments as well as those of any other department. The more lubricant, the less the squeaking on antiquated axles. What can be done as against what is done, too, frequently resolves itself into a matter of dollars. If the writer had all the funds he believed he needed, he would gather together the best C.P.A. talent in the country as a staff, or "bust" in the attempt. Perhaps, however, such a situation would lead to problems more involved and even more troublesome than those suggested, if that be possible. Results count, nothing else. If results are secured, acceptable to the department head, to the dean, to the general administration, and to the practicing brethren, it would seem that the work accomplished is beyond criticism, regardless of course content or department organization.